2001
DOI: 10.1523/jneurosci.21-09-03228.2001
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxymethamphetamine (Ecstasy)-Induced Learning and Memory Impairments Depend on the Age of Exposure during Early Development

Abstract: Use of 3,4-methylenedioxymethamphetamine (MDMA; ecstasy) has increased dramatically in recent years, yet little is known about its effects on the developing brain. Neonatal rats were administered MDMA on days 1-10 or 11-20 (analogous to early and late human third trimester brain development). MDMA exposure had no effect on survival but did affect body weight gain during treatment. After treatment, body weight largely recovered to 90-95% of controls. MDMA exposure on days 11-20 resulted in dose-related impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(173 citation statements)
references
References 63 publications
14
156
2
1
Order By: Relevance
“…These results together strengthen the notion that 5HT suppletion after serotonergic drugs such as MDMA and fenfluramine produces spatial memory impairment. In addition, support for this serotonin hypothesis also comes from animal studies that have shown impairment of spatial memory after treatment with MDMA (Sprague et al 2003; Broening et al 2001) or d-fenfluramine (Morford et al 2002 as well. Sprague et al (2003) subsequently linked the MDMA-induced serotonergic lesions in the hippocampus to deficits seen in spatial memory.…”
Section: Discussionmentioning
confidence: 98%
“…These results together strengthen the notion that 5HT suppletion after serotonergic drugs such as MDMA and fenfluramine produces spatial memory impairment. In addition, support for this serotonin hypothesis also comes from animal studies that have shown impairment of spatial memory after treatment with MDMA (Sprague et al 2003; Broening et al 2001) or d-fenfluramine (Morford et al 2002 as well. Sprague et al (2003) subsequently linked the MDMA-induced serotonergic lesions in the hippocampus to deficits seen in spatial memory.…”
Section: Discussionmentioning
confidence: 98%
“…Lower levels of dopamine metabolites were also detected in the caudate of squirrel monkeys and in the cerebral spinal fluid of women that used ecstasy [90,132]. Interestingly, either early or late neonatal (PD 1-10 or 11-20) MDMA caused subtle, yet significant, elevations in norepinephrine (7-15%) in the hippocampus of adult (PD 105) rats [11]. Even more striking, MDMA treatments to dams (GD 14 to 18) resulted in a five-fold increase in dopaminergic fiber density in the frontal cortex of offspring [76].…”
Section: Non-indoleaminementioning
confidence: 99%
“…Neonatal MDMA (PD 11-20) diminished water maze learning and novel object exploration in adult-rats [27]. However, MDMA administration at earlier postnatal periods did not alter these endpoints [11,120]. Perhaps counter-intuitively, newborn rat offspring from mothers that received MDMA during pregnancy performed better on an olfactory discrimination task.…”
Section: Learning and Memorymentioning
confidence: 99%
See 2 more Smart Citations